RESTRICTION-COMPLIANT DATA REPLICATION (2022)
Restriction-compliant data replication including receiving a request to replicate a dataset of a database that is stored in a cloud-based data warehouse at a first region of a plurality of geographic regions to a second region of the plurality of geographic regions, wherein the second region is subject to persistent storage restrictions different from restrictions of the first region; selecting a replication policy, applicable to the second region, wherein the replication policy specifies replication restrictions that conform to the persistent storage restrictions of the second region; and replicating the dataset from the first region to the second region, including applying the replication policy to the dataset.